USING OF EDGE/FOG/CLOUD COMPUTING TECHNOLOGIES IN SMART GRID INFORMATION FLOW MANAGEMENT - Azizbek Temirov; Ernazar Reypnazarov; Shakhlo Khujamatova; Umida Khojamuratova (Journals Park Publishing, 2022)
This article is an integral part of the modern life of the information society. Currently, one of the main directions of their development is the implementation of the concept of building the Internet of Things (IoT). The development of IoT includes both information and information technology acquisition technologies and the development of channels and communication networks for data transfer between these network elements.
Keywords: IoT, smart grid, fog network nodes, data processing.